Características meteorológicas de escala regional e efeitos turbulentos do vento norte no sul do Brasil - Rosa, Cinara Ewerling da (2022)
The flows induced by a complex topography influence at different scales the turbulent patterns and other meteorological aspects in the planetary boundary layer (CLP). Mainly, in southern Brazil, a geophysical flow forced by a descending topography, known as Vento Norte (VNOR; Portuguese for ”North Wind”), is characterised by the advection of warm and dry air with intense wind gusts from the north. In the present thesis the temporal and spatial scales of the VNOR and its interactions in an extensive region of southern Brazil are investigated and characterized. The study is divided into three articles. First, a significant VNOR case is analysed and its main characteristics are determined. The results show that the standard deviation of temperature is a good indicator of the beginning and demise of the VNOR phenomenon. From a micrometeorological point of view, the turbulent variables are intensified and the mechanically generated turbulence governs the evolution of the CLP. The second article identifies the frequency and spatial and temporal distribution of the VNOR phenomenon based on a climatological analysis over 11 years of observations. The study found that the average life cycle of the events is 8 hours and is directly related to the intensity of the wind gusts, i.e. the greater the magnitude of the gust reached, the longer the VNOR episode will be. The article also indicates that the VNOR phenomenon impacts a large area in the state of Rio Grande do Sul, with the characteristics being more pronounced in the region around the city of Santa Maria. The results suggest that this intensification is influenced by topographic forcing, i.e. the altimetric difference in the center of the state, which divides the plateau to the north from the central depression to the south. The third article showed that VNOR episodes force the formation of a neutral boundary layer. Under these conditions, multilevel vertical turbulent dispersion parameterisations were derived. Finally, these parameterisations were applied in a Lagrangean stochastic dispersion model to reproduce the contaminants’ concentrations observed in the neutral Praire Grass dispersion experiments.